Frozen and cold-stored platelets: reconsidered platelet products. (2nd January 2022) - Jimenez-Marco, Teresa; Castrillo, Azucena; Hierro-Riu, Fernando; Vicente, Vicente; Rivera, José
Abstract: Platelet transfusion, both prophylactic and therapeutic, is a key element in modern medicine. Currently, the standard platelet product for clinical use is platelet concentrates at room temperature (20–24°C) under gentle agitation. As this temperature favors bacterial growth, storage is limited to 5–7 days, which result in high wastage rate, and complicates inventory and product availability at remote areas. Frozen and/or cold storage would ameliorate those disadvantages by reducing the risk of bacterial contamination and by extending the product shelf-life to weeks or even years. Consequently, the usefulness in transfusion medicine of platelet cryopreservation and refrigeration, two old and scarcely used platelet storage approaches, is reemerging. Indeed, there have been substantial recent research efforts to characterize both cold and cryopreserved platelets. Most recent studies indicate that cryopreserved and cold platelets display a pro-coagulant profile that may produce the rapid hemostatic response which is needed in bleeding patients. Thus, it seems appropriate that blood banks and blood transfusion centers explore the possibility of split platelet inventories consisting of platelets stored at room temperature and cryopreserved and cold-stored platelets.